Philippine security in the age of terror: National, regional, and global challenges in the post-9/11 world - Banlaoi, Rommel C. (Animo Repository, 2009)
As the twelfth most populous nation, the Philippines’ diverse religious and ethnic population makes it an ideal example of the changing tenet of what is deemed national security—post 9/11. Issues previously considered social or public are now viewed as security issues. Food production is now analyzed in the context of food security and environmental degradation is now a part of environmental security. This broadened perspective is not unique to the Philippines, but—thanks to the island nation’s long struggle with issues of Muslim radicalism, democracy, and globalization—it serves as a model worth studying. And no one is better positioned to take on this study than Rommel C. Banlaoi, Chairman and Executive Director of the Philippine Institute for Peace, Violence, and Terrorism Research. © 2010 by Taylor & Francis Group, LLC.